2012
DOI: 10.1177/1362168812455586
|View full text |Cite
|
Sign up to set email alerts
|

Quality and quantity of oral participation and English proficiency gains

Abstract: There are many reasons to believe that oral participation in the target language (TL) is beneficial for classroom language learners. In addition to the prominence current second language acquisition (SLA) theory gives to processes that assume learner production of the TL (e.g. negotiation of meaning), teachers often view oral participation as a measure of learner involvement. Thus, it is often assumed that learners who participate often are likely to make greater proficiency gains. This correlational study exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…In foreign language (FL) and L2 research, classroom participation has generally been conceived of in terms of students' L2 verbal activity in class. Studies on L2 interaction and production have provided support for the use of learners' output as evidence of L2 learning (Kumaravadivelu, ), and, as a consequence, classroom participation has been linked to speaking and language practice (Delaney, ; Johnson, ), which, in turn, have been found to lead to higher levels of communicative competence and achievement (MacIntyre, Baker, Clément, & Donovan, ; Shintani, Li, & Ellis, ; Tsou, ). Indeed, according to Dörnyei (2005), learning, including L2 learning, “relies heavily on learning through participatory experience in communication” (p. 210).…”
Section: Review Of Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…In foreign language (FL) and L2 research, classroom participation has generally been conceived of in terms of students' L2 verbal activity in class. Studies on L2 interaction and production have provided support for the use of learners' output as evidence of L2 learning (Kumaravadivelu, ), and, as a consequence, classroom participation has been linked to speaking and language practice (Delaney, ; Johnson, ), which, in turn, have been found to lead to higher levels of communicative competence and achievement (MacIntyre, Baker, Clément, & Donovan, ; Shintani, Li, & Ellis, ; Tsou, ). Indeed, according to Dörnyei (2005), learning, including L2 learning, “relies heavily on learning through participatory experience in communication” (p. 210).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Indeed, according to Dörnyei (2005), learning, including L2 learning, “relies heavily on learning through participatory experience in communication” (p. 210). In general, the common principle that underlies perspectives on L2 interaction is that oral production provides a milieu in which L2 acquisition processes can take place (Delaney, ; Swain, ). Nonetheless, this idea has not gone undisputed by proponents of theories that emphasize the role of input in L2 learning.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…When designing the virtual scenarios, the designed scenarios mustn't go against the real-life experience of students, but should be in line with the daily routines that are closely related to students [29]. The clear scenario settings and definite interpersonal relationships of VST allow students to experience the real relationships in true situations, feel the charm of language in communication, make language learning vivid and interesting, and improve students' spoken English learning efficiency [30]. The value of VST in spoken English teaching…”
Section: Application Of Vst In Spoken English Teachingmentioning
confidence: 99%
“…While some studies have focused on how student participation can be improved, other researchers examined the relationship between the participation and students' outcomes. For example, a study carried out in a Japanese university showed that there was a positive correlation between the quality of student oral participation (accuracy, complexity, and fluency) and the gains in target language ability, but no correlation between the quantity of participation and the gains in target language ability (Delaney, 2012). It was explained that the accurate and complex utterances required students to engage in more intensive processing, which resulted in greater gains in the ability of the target language and in the fluency of target language.…”
Section: Participation In Ellmentioning
confidence: 99%